Aesthetic Appreciation Is Different: Aesthetic Pleasure in Architectural Aesthetics - Lei Pei; Zihao Cao (Buildings, 2025)
Architectural aesthetics is often studied with a focus on the visual properties of buildings, yet the role of individual aesthetic appreciation abilities in shaping aesthetic pleasure remains overlooked. This study challenges the traditional object-centric perspective by investigating how aesthetic appreciation ability influences architectural aesthetic pleasure through aesthetic judgment. Using Hui-style architecture, a distinctive architectural style originating from the Huizhou region in southern China, as the representative case, a questionnaire survey was conducted with 453 participants. Regression analysis was applied to examine the moderating effects of aesthetic judgment (variety, unity, novelty, and typicality) on the relationship between aesthetic appreciation ability and aesthetic pleasure. The results reveal that individuals with high aesthetic appreciation ability experience greater aesthetic pleasure when exposed to diverse and novel architectural elements. In contrast, those with low aesthetic appreciation ability respond primarily to novelty, showing limited sensitivity to other aesthetic judgments. These findings highlight the nuanced interplay between personal aesthetic capacities and architectural experience, offering valuable insights for artists, architects, and educators seeking to cater to diverse aesthetic preferences and enhance public engagement with architectural beauty.